Effect of Stress Level Among Medical Students Doing Thesis to Academic Achievement in Sebelas Maret University - Priharyuni, Chrystina Yurita; ., Maryani; Wicaksono, Bagus (Nexus Pendidikan Kedokteran dan Kesehatan, 2015)
Background: Stress is a condition when people feels threatened or pressured, either physically or mentally. Stress is affected by many factors. Students who are working on the thesis are highly susceptible to stress. Stress can cause a variety of effects can disrupt the learning process, so it can affect academic achievement. This study aims to determine the influence of stress level in students doing thesis to academic achievement among medical student of Sebelas Maret University. Methods: This research was an observational analytic study with cross sectional study approach. The subjects were medical students of Sebelas Maret University who are doing thesis with 140 samples. Stress level was measured by questionnaire, whereas academic achievement was measured by Grade Point Average on study results. Data was analyzed using Kendallâs Tau correlation test. Results: The result for correlation test were correlation value (r) -0.069 and p = 0.123 (p > 0.05). It means there was no significant relationship between the stress level and Grade Point Average. Conclusions: There is no significant effect of stress level in students doing thesis to academic achievement among medical student of Sebelas Maret University. Keywords: Stress level, thesis, academic achievement Â